To Lend is to Own: A Game Theoretic Analysis of the E-Book Lending Market. Issue 3 (3rd July 2017) - Chen, Li; King, Ruth C.
ABSTRACT: Digital forms of content have provided online retailers new ways of enhancing other business opportunities. E-book vendors such as Amazon introduced a fourteen-day lending program for its Kindle-linked e-books, banking on the e-book lending program to increase sales to consumers who appreciate the added utility from the new lending options. The benefits of such an e-book lending strategy can become significant as the number of e-book owners reaches a critical mass, creating a network effect. However, the strategy may involve risk because there is also the possibility of cannibalization of retailers' print book. We investigate, in both monopolistic and duopolistic competition settings, whether and how an online retailer can benefit from introducing an e-book lending program and its effect on their pricing strategy and cannibalization. We also examine whether sequential release of print books and e-books in monopolistic settings will affect retailer's revenue. Our study finds that in a monopoly setting, the retailer should implement the e-book lending strategy when the condition of network effect is satisfied. Our findings also suggest that retailers can use release time to minimize cannibalization in the case of sequential release. In addition, the e-book lending option benefits the retailer in a duopoly setting only when one retailer offers such a program; otherwise, the better-known retailer benefits more. Theoretical and practical implications for the management of different formats of content in various competition markets to sustain and expand business opportunities are discussed.